FUNGSI TRADISI MA’BARU’TUNG DI DESA PAROMBEAN KECAMATAN CURIO KABUPATEN ENREKANG - Najamuddin, Najamuddin; Ahmadin, Ahmadin; Halfiah, Halfiah (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2023)
This article discusses the diverse Ma'baru'tung tradition in Parombean Village, Curio District, Enrekang Regency. This research aims to identify the functions of the Ma'baru'tung tradition within the local community context. The study adopts a qualitative approach by collecting data through participatory observation and interviews with indigenous figures and local community members. The research findings indicate that the Ma'baru'tung tradition serves several essential functions within the community, including as a form of entertainment that enriches local cultural life, a means of communication to convey social and historical messages, and a ritual that connects people with nature and their ancestors. Additionally, tradition plays a role in strengthening social bonds and community integration, while also serving as an educational medium to impart traditional values. The study concludes that the Ma'baru'tung tradition plays a significant role in preserving the cultural and social identity of Parombean Village's community, making it imperative to preserve and promote it for the cultural heritage's sustainability in the future.